The record precipitation and flood event in Iberia in December 1876: description and synoptic analysis - Trigo, Ricardo M.; Varino, Filipa; Ramos, Alexandre M.; Valente, Maria A.; Zêzere, José L.; Vaquero, José M.; Gouveia, Célia M.; Russo, Ana (Frontiers in Earth Science, 2014)
The first week of December 1876 was marked by extreme weather conditions that affected the south-western sector of the Iberian Peninsula, leading to an all-time record flow in two large international rivers. As a direct consequence, several Portuguese and Spanish towns and villages located in the banks of both rivers suffered serious flood damage on 7 December 1876. These unusual floods were amplified by the preceding particularly autumn wet months, with October 1876 presenting extremely high precipitation anomalies for all western Iberia stations. Two recently digitised stations in Portugal (Lisbon and Evora), present a peak value on 5 December 1876. Furthermore, the values of precipitation registered between 28 November and 7 December were so remarkable that, the episode of 1876 still corresponds to the maximum average daily precipitation values for temporal scales between 2 and 10 days. Using several different data sources, such as historical newspapers of that time, meteorological data recently digitised from several stations in Portugal and Spain and the recently available 20th Century Reanalysis, we provide a detailed analysis on the socio-economic impacts, precipitation values and the atmospheric circulation conditions associated with this event. The atmospheric circulation during these months was assessed at the monthly, daily and sub-daily scales. All months considered present an intense negative NAO index value, with November 1876 corresponding to the lowest NAO value on record since 1865. We have also computed a multivariable analysis of surface and upper air fields in order to provide some enlightening into the evolution of the synoptic conditions in the week prior to the floods. These events resulted from the continuous pouring of precipitation registered between 28 November and 7 December, due to the consecutive passage of Atlantic low-pressure systems fuelled by the presence of an atmospheric-river tropical moisture flow over central Atlantic Ocean.